Ultra-sensitive ppb-level methane detection based on NIR all-optical photoacoustic spectroscopy by using differential fiber-optic microphones with gold-chromium composite nanomembrane - Hanping Xiao; Jinbiao Zhao; Chaotan Sima; Ping Lu; Yanhong Long; Yan Ai; Wanjin Zhang; Yufeng Pan; Jiangshan Zhang; Deming Liu (Photoacoustics, 2022)
In this paper, we propose and experimentally demonstrate an ultra-sensitive all-optical PAS gas sensor, incorporating with a near-infrared (NIR) diode laser, fiber-optic microphones (FOMs) and a double channel differential T-type photoacoustic cell. The FOM is realized by Fabry-Perot interferometry and novel gold-chromium (Au-Cr) composite nanomembranes. To meet the demand of high sensitivity and flat frequency response for the FOMs, the Au-Cr composite diaphragm is deliberately designed and fabricated by E-beam evaporation deposition with 330 nm in thickness and 6.35 mm in radius. Experimental results show that the FOM has a sensitivity of about 30 V/Pa and a flat frequency response from 300 to 900 Hz with fluctuation below 1 dB. Moreover, a double channel differential T-type photoacoustic cell is designed and employed in the all-optical PAS gas sensor, with the first-order resonant frequency of 610 Hz. The all-optical gas sensor is established and verified for CH4 detection and the normalized noise equivalent absorption (NNEA) is 4.42 × 10−10 W∙cm−1∙Hz−1/2. The minimum detection limit (MDL) of 36.45 ppb is achieved with a 1 s integration time. The MDL could be further enhanced to 4.87 ppb with an integration time of 81 s, allowing ultra-sensitive trace gas detection.